2018
DOI: 10.1016/j.ssci.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Safety management systems from Three Mile Island to Piper Alpha, a review in English and Dutch literature for the period 1979 to 1988

Abstract: Introduction Materials and methods Three Mile Island Generic management approaches Total Quality Management Occupational safety Occupational safety: state of the art Occupational safety: theory, and models Process safety Technical process safety Man-machine interactions in complex technological systems Safety management and safety management systems

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…There have been a few reviews on safety in specific countries or accidents (Oostendorp et al, 2016;Swuste et al, 2018Swuste et al, , 2016Swuste et al, , 2014Swuste et al, , 2010, but there has been no review on HFE methods and approaches applied to the nuclear industry in general since Stanton (1996). The current paper, therefore, aims to provide an up-to-date critical analysis of past and current HFE research for nuclear safety and outline a set of future directions for research and practice.…”
Section: Human Factors and Nuclear Safetymentioning
confidence: 99%
“…There have been a few reviews on safety in specific countries or accidents (Oostendorp et al, 2016;Swuste et al, 2018Swuste et al, , 2016Swuste et al, , 2014Swuste et al, , 2010, but there has been no review on HFE methods and approaches applied to the nuclear industry in general since Stanton (1996). The current paper, therefore, aims to provide an up-to-date critical analysis of past and current HFE research for nuclear safety and outline a set of future directions for research and practice.…”
Section: Human Factors and Nuclear Safetymentioning
confidence: 99%
“…Within the beginning stages of the Three Mile Island incident, over 100 alarms were triggered, causing the operators to react to an overload of information. In adequate training and deficiencies in condition monitoring protocols were cited as contributing human factors in the incident [49].…”
Section: Condition Monitoringmentioning
confidence: 99%
“…It also provides an overview on the shortcomings of conventional quantitative risk assessment, which has not been improved since the early 1980s. Swuste et al (2018) carried out a similar study that overviewed safety management systems, models for gas incidents across the industries. Given the limitations of past approaches, the review paper suggested a dynamic risk assessment to apply realistic data for case studies.…”
Section: Remarkable Past Researchmentioning
confidence: 99%